“The Jenny and the Colt” in Matthew’s Messianic Entry, Part 2: Matthew 21:7 as a Reading of Mark 11:7 in Light of Zechariah 9:9. - CARLSON, STEPHEN C. (Catholic Biblical Quarterly, 2019)
Matthewâ€™s description of Jesus taking his mount in 21:7 as â€œand he sat on top of themâ€ has been a crux interpretum for centuries. Some take it literally even though it is impossible for a human to sit on two donkeys at once. Others try to avoid the problem by referring the plural pronoun â€œthemâ€ to the coats the disciples placed on the donkeys instead. I contend that both readings are unsatisfactory, and I bring new evidence and arguments, including Matthewâ€™s plenary reading of Zech 9:9 set forth in part 1 of the study (see CBQ 81 [2019] 62-84), to argue that the plural pronoun functions for Matthew as a whole-for-part synecdoche, where the jenny and the colt constitute a conceptual whole such that when Jesus sits on top of â€œthem,â€ he takes his mount on the part that fulfills the Hebrew prophecy.